A HOSPITAL BASED PRELIMINARY REPORT ON SLEEP DISORDERED BREATHING IN PAKISTANI POPULATION - Haqqee, R.; Hussain, S. F.; Mujib, M.; Ahmad, H. R. (Journal of Ayub Medical College Abbottabad, 2002)
Background: Sleep Disordered Breathing is an important medical condition leading to significant morbidity and mortality. Western studies have shown its prevalence in middle age to be 9% in women and 24% in men. The aim of this study was to have a preliminary assessment on the frequency of Sleep Disordered Breathing in Pakistani subjects. Method:Patients attending a medical clinic were surveyed. A sleep questionnaire elicited information about snoring, witnessed apnoea, nocturnal choking and excessive daytime sleepiness. Data were recorded for age, height, collar size and weight. Epworth Sleepiness Scale was used to assess excessive daytime sleepiness. Statistical analysis was by chi square test, t-test and Fisher’s exact test. A p-value less than 0.05 was considered significant. Results: A total of 123 subjects (M:F= 2:1) were included in the study. The frequency of snoring was found to be 46%. Snoring with apnoea was reported in 7% and snoring with apnoea and excessive daytime sleepiness in 3%. Snorers were more obese (p<0.001), older (p<0.003), with higher body mass index (p<0.001) and larger collar size (p<0.006) than non-snorers. Hypertension was more common in patients with sleep disordered breathing (35%) as compared to those without (16%). Conclusions: This is the first preliminary data on sleep disordered breathing from Pakistan that reflects that the prevalence is similar to that seen in the West. The risk factors and association with hypertension are also comparable. Key Words: sleep disordered breathing; obstructive sleep apnoea; snoring; prevalence; Pakistan